System for monitoring microclimate conditions in greenhouse - Marković Dušan B.; Pavlović Radoš M.; Pešović Uroš M.; Ranđić Siniša S. (Acta Agriculturae Serbica, 2014)
Monitoring microclimate parameters in different kind of environments has significant contribution to many areas of human activity and production processes. One of them is vegetable production in greenhouses where measurement of its microclimate parameters may influence the decision on taking appropriate action and protect crops. It is also important to preserve optimal condition in greenhouses to facilitate the process of transpiration, plant mineral nutrition and prevent of a variety physiological damage caused by a deficit of some specific nutrients. Systems for monitoring have wide application in the last years thanks to development of modern computer technology. In this paper model of the monitoring system based on smart transducer concept was introduced. Within the system components are based on MSP430 ultra low power micro controllers. They are using wireless communication to exchange data within the system that was structured according to smart transducer concept. User applications from the network could access to system interface using HTTP protocol where web server could be running on the computer or it could be an embedded web server running on micro controller based device.